Electrical Properties of Pulmonary Lymphatic Smooth Muscle Cells - Ahmadzai, Mustafa (The Meducator, 2012)
Mustafa Ahmadzai is a fourth-year student in the Honours Biology and Pharmacology (Co-op) Program. Mustafa spent this previous summer working at the Firestone Institute for Respiratory Health at St. Joseph’s Hospital in downtown Hamilton. His research focused on the electrophysiological properties of lymphatic smooth muscle cells in the lungs and how they participate in the etiology of asthma and other related pulmonary diseases. The work involved using a technique known as voltage clamping, wherein electrical probes are used to stimulate isolated cells and measure the resulting currents. Like pieces to a puzzle, these electrical responses may give us an insight into how the tissue behaves under complex disease states like asthma and chronic obstructive pulmonary disorder (COPD).